2009
DOI: 10.1016/j.neuroscience.2009.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in phenotype definition in the whole-genome era: multivariate models of memory and intelligence

Abstract: Refining phenotypes for the study of neuropsychiatric disorders is of paramount importance in neuroscience. Poor phenotype definition provides the greatest obstacle for making progress in disorders like schizophrenia, bipolar disorder, Attention Deficit/Hyperactivity Disorder (ADHD), and autism. Using freely available informatics tools developed by the Consortium for Neuropsychiatric Phenomics (CNP), we provide a framework for defining and refining latent constructs used in neuroscience research and then apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 117 publications
1
43
0
Order By: Relevance
“…The first generation of GWA studies have indicated that traditional psychiatric diagnostic phenotypes might not provide the most powerful means of mapping disease loci (Sabb et al, 2009). It is becoming increasingly apparent that within diagnostic categories, such as bipolar disorder and schizophrenia, extensive aetiological and genetic heterogeneity operates (O'Donovan et al, 2009).…”
Section: Phenotypic Refinementmentioning
confidence: 99%
“…The first generation of GWA studies have indicated that traditional psychiatric diagnostic phenotypes might not provide the most powerful means of mapping disease loci (Sabb et al, 2009). It is becoming increasingly apparent that within diagnostic categories, such as bipolar disorder and schizophrenia, extensive aetiological and genetic heterogeneity operates (O'Donovan et al, 2009).…”
Section: Phenotypic Refinementmentioning
confidence: 99%
“…In their review, Sabb et al (2009) concluded that genetic associations had thus far accounted for only about 7% of the variance in a variety of memory measures.…”
mentioning
confidence: 99%
“…Although the first-generation GWAS in AD indicated that psychiatric and cognitive function used as endophenotypes do not provide a powerful means of mapping disease loci [27,28], which was not completely a surprise given the extensively negative results of GWAS in several psychiatric disorders [29,30], the incorporation of clinical and neuropathological information into GWAS has proven successful. Several studies have now reported on data from the ADNI (Alzheimer's Disease Neuroimaging Initiative) database, which is ideal for endophenotype studies in AD, since it brings together MRI (magnetic resonance imaging), PET (positron emission tomography), genetic factors, other biological markers and clinical and neuropsychological assessments of the same samples.…”
Section: Brief Overview Of Ad Genetics: Focus On the Recent Gwas Resultsmentioning
confidence: 99%